Performance of cs-sleeve under direct tensile load: part II: structural performance - Ling, Jeng Hua; Abd. Rahman, Ahmad Baharudin; Mirasa, Abdul Karim; Abd. Hamid, Zuhairi (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2008)

(untitled)
Tensile resistance of a sleeve connector used to connect between two structural components by confining grouted reinforcement bars relies on interaction among reinforcement bars, sleeve and grout. In this study, a total of nine specimens with different configurations, sizes of sleeves, reinforcement bars’ surface conditions and also grouting materials were tested under direct tensile tests. This paper presents further discussion on the study of performance of CSSleeves, particularly on the load-displacement graphs and load-strain graphs of the specimens in order to acquire the structural performance of the specimens. The test data indicates that threads on reinforcement bar had significantly deteriorated the bonding mechanism between reinforcement bars and grout. None of the specimens achieved the required strength. However, the findings obtained from the study provide essential basis for future research in developing an adequate sleeve connector.